FLEXIBLE LEARNING IN TRADITIONAL EDUCATIONAL PROCESS - I. N. GOLITSYNA (Высшее образование в России)
The article discusses the conception of “flexible learning” in the context of implementation in traditional educational process. The author highlights the experience of flexible learning organization in the learning process of the students of the educational programs “Applied Informatics” (bachelor level) and “Information Systems and Technology” (bachelor level) by using web resources for practical training. Flexible learning provides additional opportunities for students’ independent work, provides individual control over solving of tasks, allows using personalization in the framework of traditional academic learning. Flexible learning improves the techniques of students’ self-education and long-life education and advances the development of IT professionals’ competencies. It helps students to develop personally-oriented electronic information-educational environment including using of mobile devices.